Sense of coherence and quality of life in adolescents with heart disease - Coutinho,Virgínia Menezes (2022)
Abstract Objective: The aim of this study was to assess the association between the Sense of Coherence (SoC) and Quality of Life (QoL) in adolescents with heart disease. Methods: A cross-sectional study was carried out with 164 adolescents with congenital or valvular heart disease, aged between 10 and 18 years, treated in a referral center in the city of Recife – Brazil. The information collected contains census data, type of heart disease, economic status identified according to the Brazilian Criteria for Economic Classification (ABEP), as well as an evaluation of the SoC and the QoL. Results: The SoC (50.09) and QoL (72.23) exhibited high average scores. The SoC was positively correlated with all dimensions of the QoL scale (p<0.001). The social and school dimensions, respectively, presented the highest and lowest scores. The linear regression analysis revealed that the SoC influenced the school and emotional dimensions. Conclusions: This study demonstrates that the SoC is a protective factor in the life of adolescents. This factor helps on the improvement of perception of QoL and on successfully dealing with daily adversities and chronic stress.